Challenges in the Clinical Management of a Substantial Antrochoanal Polyp: A Case Report of Persistent Anatomical Obstruction in a 17-Year-Old Male - Wardhany, Salsa Ratia; Surya, Guntur (Jurnal Ners, 2024)
Antrochoanal polyps (ACPs) are predominantly benign growths originating from the mucosal lining of the maxillary antrum, constituting a minor percentage of nasal polyps. This case report examines a unique presentation of a substantial ACP in a 17-year-old male, highlighting the challenges in achieving resolution despite attempted medical intervention. The patient, despite seeking medical attention and undergoing surgery, experienced persistent nasal obstruction and related symptoms. Clinical examinations and imaging revealed a sizable ACP causing pronounced obstruction within the sinonasal complex, emphasizing the potential impact of these polyps on multiple anatomical regions. Computed tomography scans delineated additional sinonasal pathologies, including sinusitis, nasal concha hypertrophy, and nasal septal deviation. These findings underscore the complexity of ACP cases and the need for comprehensive diagnostic assessments. The patient is currently undergoing pharmacological management with cetirizine and tranexamic acid, aiming to alleviate symptoms. A scheduled Functional Endoscopic Sinus Surgery (FESS) underscores a holistic therapeutic approach to address underlying sinus issues and optimize long-term health. ACPs, though rare, present challenges in diagnosis and management. Swift and accurate diagnosis is crucial to mitigate potential complications, and a nuanced understanding of the interplay between ACPs and chronic sinusitis enhances diagnostic accuracy. The lack of response to previous treatments underscores the necessity for adaptive therapeutic strategies. This case highlights the intricate nature of ACPs, emphasizing the importance of a comprehensive diagnostic approach and a tailored therapeutic strategy. Ongoing research into disease mechanisms contributes to the expeditiousness and accuracy of diagnostic approaches, optimizing the overall management of ACPs and improving patient outcomes.